Axiological problematics implementation of multicultural Islamic education in public schools - Mufidul Abror; An'im Fattach (Sean Institute, 2024)
In general educational institutions, normative-conceptual Islamic religious education is intended as an effort to build and foster diversity in the form of an attitude of accepting differences, tolerance towards ethnic, cultural and religious differences. This research attempts to describe and describe the phenomena that occur in accordance with the circumstances. actually in the field which aims to identify and formulate solutions to the axiological problems of implementing multicultural Islamic education in public schools. based on existing literature using qualitative descriptive methods with a library research approach. Data was found that the implementation problem in this problem is that Islamic education has not been able to prepare a generation that is in line with the progress of the times, the fading of the initial doctrine of education among educators and educational staff and its erosion the values of ihsan, mercy and trust.